Economic Evaluations of Treatments for Inflammatory Bowel Diseases: A Literature Review - Lachaine Jean; Miron Audrey; Catherine Beauchemin; on behalf of the iGenoMed Consortium (Canadian Journal of Gastroenterology and Hepatology, 2018)
Objective. The objective of this literature review was to evaluate the existing evidence regarding the cost-effectiveness of treatment options in IBD. Methods. A systematic review of the literature was conducted to identify economic evaluations of IBD therapy. The literature search was performed using electronic databases MEDLINE and EMBASE. Searches were limited to full economic evaluations published in English or French between 2004 and 2016. Results. A total of 5,403 potentially relevant studies were identified. After screening titles and abstracts, 48 studies were included, according to the eligibility criteria. A total of 56% and 42% of the studies were assessing treatments of UC or CD, respectively. Treatment options under evaluation included biological agents, mesalamine, immunosuppressants, and surgery. The majority of studies evaluated the cost-effectiveness of biological treatments. Biological therapies were dominant in 23% of the analyses and were cost-effective according to a $CAD50,000/QALY and $CAD100,000/QALY threshold in 41% and 62% of the analyses, respectively. Conclusion. This literature review provided a comprehensive overview of the economic evaluations for the different treatment options for IBD over the past 12 years and represents a helpful reference for future economic evaluations.